Evaluasi Perencanaan Strategis di Rumah Sakit Umum Daerah Sanjiwani Gianyar dalam Upaya Peningkatan Kualitas Pelayanan - Dewa Made Budi Subagia; Anak Ayu Sri Saraswati; Putu Vierda Lya Suandari (Journal Of Administration and Educational Management (ALIGNMENT), 2024)
This research aims to determine the evaluation of strategic planning in an effort to improve the quality of services at the Sanjiwani Gianyar regional general hospital. This research method was carried out using a descriptive qualitative approach using interview data collection methods and document review. The preparation of strategic planning at the Sanjiwani Gianyar Regional General Hospital begins with establishing a vision and mission, then a SWOT analysis is carried out, consisting of strengths, weaknesses, opportunities and threats, the gradual implementation of a business strategic plan carried out over five years every year. The process in implementing the annual strategic planning work program carried out by the hospital includes the procurement and improvement program for hospital facilities, maintenance of hospital infrastructure, purchase program for health support equipment, formal education and training, procurement of room equipment, building rehabilitation program. This is related to the quality of services provided such as BOR (bed occupancy rate), BTO (bed turn over) LOS (length of stay), TOI (turn over interval), NDR (net death rate), GDR (gross death rate), Implementation of strategic planning begins with socialization to units in the hospital and each unit has duties and responsibilities in carrying out strategic planning in accordance with the main tasks and each unit. Conclusion, evaluation is carried out at the end of each year to see the results of the implementation of activities and as input for making improvements in the coming year, evaluation is also carried out through supervision and monitoring in inpatient, emergency room and outpatient care Keywords: Strategic Planning Evaluation, Service Quality